SOCIOCULTURAL MISSION OF THE UNIVERSITY IN THE CONTEXT OF THE REGION DEVELOPMENT - Dmitry N. Bezgodov; Oksana I. Belyaeva (Высшее образование в России, 2016)
The article explores the role of the University in creating an auspicious sociocultural environment that is conducive to solution of topical Russian problem of single-industry towns. The authors consider some specific forms of work, projects, initiatives of the Ukhta State Technical University, which promote socio-economic development of the city and the region.